Molecular characterization of S. japonicum exosome-like vesicles reveals their regulatory roles in parasite-host interactions - Zhu, Lihui (Sci Rep, 2016)
Secreted extracellular vesicles play an important role in pathogen-host interactions. Increased knowledge of schistosome extracellular vesicles could provide insights into schistosome-host interactions and enable the development of novel intervention strategies to inhibit parasitic processes and lessen disease transmission. Here, we describe biochemical characterization of Schistosoma japonicum exosome-like vesicles (S. japonicum EVs). A total of 403 proteins were identified in S. japonicum EVs, and bioinformatics analyses indicated that these proteins were mainly involved in binding, catalytic activity, and translation regulatory activity. Next, we characterized the population of small RNAs associated with S. japonicum EVs. Further studies demonstrated that mammalian cells could internalize S. japonicum EVs and transfer their cargo miRNAs to recipient cells. Additionally, we found that a specific miRNA, likely originating from a final host, ocu-miR-191–5p, is also associated with S. japonicum EVs. Overall, our findings demonstrate that S. japonicum EVs could be implicated in the pathogenesis of schistosomiasis via a mechanism involving the transfer of their cargo miRNAs to hosts. Our findings provide novel insights into the mechanisms of schistosome-host interactions.